Infrastructure Model Volunteered Geographic Information Social Assistance Program To Support eGovernment Case Study of Central Aceh District - Hendri Syahputra; Alfitra Alfitra (International Journal of Engineering, Science and Information Technology, 2022)
The government's role in providing social assistance to reduce poverty has been going very well. However, in practice, there are obstacles to collecting and verifying data on prospective beneficiaries, so fast, precise, and accurate information is needed through the participation of the Community or Community to provide information regarding potential beneficiaries—social assistance. This study's goal is to create and develop a model of the Volunteered Geographic Information (VGI) system involving the participation of the Community to determine the effectiveness of the distribution of social assistance by the government and to support the role of a transparent government or good government. This research method is descriptive research with quantitative and qualitative descriptive approaches. This system also refers to the design, development, and stages of the VGI system process suitable for a crowd or community-based approach. The expected result is a VGI-based geographic information system: First: Collect and observe data on social assistance recipients in Aceh Tengah district, Aceh Province. Second: Designing and implementing a VGI-based geographic information system. Third: System testing through two stages: system functional and non-functional testing. The final results of this research are a web-based VGI Social Assistance system model and, for volunteers, the Android-based VGI Social Assistance application.